Investigations of Magnetic and Structural Order in Molecular-based Inorganic Framework Materials - Geers, Madeleine (2024)
This thesis explores the role composition plays on the crystallographic structures of molecular-based frameworks and how, in turn, this influences their magnetic character. Whilst it is understood that the combination of atomic anions and cations selected to build inorganic compounds impacts the connectivity and physical properties of materials, anticipating the relationship for molecular-based frameworks is less reliable. A method to probe both the crystallographic and magnetic structure of compounds simultaneously is by neutron diffraction experiments, which is a technique of particular focus in this work.